1974
DOI: 10.1037/h0036949
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde amnesia: Storage failure versus retrieval failure.

Abstract: dence which suggests that the results of these studies may have little bearing on memory consolidation issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 24 publications
6
68
1
Order By: Relevance
“…Some researchers (see Gold and King 1974), however, have argued that reminder effects are not inconsistent with traditional consolidation theory. They take the view that the previously described residual memories are reactivated by the reminder stimuli and new learning results from the conjoint activation of the reactivated (old/weak) memories and the neural representation of the reminder stimuli (which typically are selected to avoid any physical pairing of the two associates constituting the target memory).…”
Section: Accounts Of Experimental Amnesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers (see Gold and King 1974), however, have argued that reminder effects are not inconsistent with traditional consolidation theory. They take the view that the previously described residual memories are reactivated by the reminder stimuli and new learning results from the conjoint activation of the reactivated (old/weak) memories and the neural representation of the reminder stimuli (which typically are selected to avoid any physical pairing of the two associates constituting the target memory).…”
Section: Accounts Of Experimental Amnesiamentioning
confidence: 99%
“…Thus, reminder effects suggest that amnestic agents do not interfere with consolidation of the central dyadic relationship between the CS and US. In defense of the consolidation view of experimental amnesia, Gold and King (1974) have argued that, although reminder treatments do not alter behavior in naive animals, they do enhance performance with weakly performing subjects (sometimes misidentified as weakly trained subjects). That is, they argue that reminder treatments seem to enhance performance even when there is no impairment.…”
Section: Learning and Memory 493mentioning
confidence: 99%
“…Critical-differences tests (Lindquist, 1956) were used to compare the individual treatment conditions. These tests showed that the ECS-NR animals had significantly Contrary to the argument of Gold and King (1974), it is possible, apparently, to alleviate such amnesia without supplying an animal with additional information that is compatible with prior learning. In the absence of such additional compatible information, a storage failure hypothesis would have to predict that ECSinduced amnesia should be permanent.…”
Section: Design and Proceduresmentioning
confidence: 85%
“…However, Gold and King (1974) suggest that it is the combination of these factors that produces improved retention in ECS-treated animals. Thus, according to this interpretation, ECS produces a partial loss of information from storage, but the lost information is replaced by compatible information acquired during the reminder treatment.…”
Section: Gordon and Mowrermentioning
confidence: 99%
See 1 more Smart Citation